Mending Nona's Pia - Neuberger, Mary (My University, 2018)
MENDING NONA'S PIÑA takes its title from the artist's attempt to mend an heirloom cloth made by native Filipino weavers with strands of her hair, suggesting how forces of colonialism enabled trauma and abuse across generations in her family. Weaving her hair into natural materials and settings, MJ Neuberger posits a return to an indigenous body/self that is abandoned in abuse and Othered by colonization. Combining her tears with water blessed in a native healing ritual, she suggests the transformative power of grief.
Keywords: abuse; body; colonialism; grief; indigenous; trauma